2017
DOI: 10.1039/c7en00154a
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of B(α)P on carbon nanopowder affects accumulation and toxicity in zebrafish (Danio rerio) embryos

Abstract: The interactions of nanomaterials with contaminants represent great concern for the environment and human health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 71 publications
1
7
1
Order By: Relevance
“…While other studies have demonstrated potentiation of the response to PAHs by co-exposure to graphene-based materials, 5557 we observe only a reduction in bioavailability and cellular responses. 26, 58 One of the challenges in comparing different studies is the wide variety of two-dimensional graphene-based nanomaterials and choice reference materials for comparison.…”
Section: Discussioncontrasting
confidence: 94%
See 1 more Smart Citation
“…While other studies have demonstrated potentiation of the response to PAHs by co-exposure to graphene-based materials, 5557 we observe only a reduction in bioavailability and cellular responses. 26, 58 One of the challenges in comparing different studies is the wide variety of two-dimensional graphene-based nanomaterials and choice reference materials for comparison.…”
Section: Discussioncontrasting
confidence: 94%
“…56 In an in vivo model of exposure, co-exposure to a flake-like carbon nanopowder enhanced the uptake of and response to benzo(a)pyrene, leading to increased numbers of apoptotic and necrotic cells. 55 In prior studies like these examples, carbon nanomaterials appear to have a “Trojan-horse” effect where adsorption of the aromatic pollutant leads to enhanced uptake, response, and toxicity. 60 At high concentrations, carbon nanomaterials, including 2D graphene-base materials, can also induce adverse effects that can confound the study of mixtures.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in the bioavailability of contaminants co-exposed with carbon nanomaterial have been reported, from a decrease in bioavailability [78,79] to its enhancement, also called the “carrier effect” [80,81]. It has been demonstrated that carbon nanopowder helps B[a]P uptake by zebrafish embryos and very interestingly also affected the distribution of the pollutant in the organism [82]. However, in the same species, in zebrafish larvae, it has been shown that bioavailability of 17α-ethynylestradiol (EE2) was reduced with increasing concentration of n C 60 nanoparticles [14].…”
Section: Resultsmentioning
confidence: 99%
“…Another hypothesis to explain the lack of EROD modulation is related to the low inducibility of cytochrome P4501A (CYP1A) in developing embryos. Indeed, a recent study in which embryos (96 hpf) were exposed to different concentrations of the CYP1A inducer benzo(α)pyrene (B(α)P) showed only a low increase of cyp1a gene transcription at the concentration of 20 μg L -1 (Della Torre et al, 2017). Moreover, a previous study by Saad et al (2016), which aimed to determine the biotransformation potential of zebrafish embryos during their critical window for teratogens, observed a very low CYP1A activity during organogenesis.…”
Section: Resultsmentioning
confidence: 99%